2020
DOI: 10.1021/acschemneuro.0c00199
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin-2-Dependent Mechanism of GPR52 Signaling in Frontal Cortical Neurons

Abstract: The orphan Gαs-coupled receptor GPR52 is expressed exclusively in the brain, predominantly in circuitry relating to symptoms of neuropsychiatric and cognitive disorders such as schizophrenia. While GPR52 agonists have displayed antipsychotic and procognitive efficacy in murine models, there remains limited evidence delineating the molecular mechanisms of these effects. Indeed, previous studies have solely reported canonical cAMP signaling and CREB phosphorylation downstream of GPR52 activation. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In contrast, Setoh et al identified another GPR52 agonist, compound 7m, and found that it dose dependently increased [cAMP] i concentrations in CHO cells expressing GPR52 (Setoh et al, 2014). The cAMPincreasing effect of c11 in HEK293 cells expressing GPR52 in our present study was consistent with the result by Setoh et al In addition, recent studies found that 3-BTBZ, another agonist of GPR52, potently increased [cAMP] i in a b-arrestin 2 independent manner in frontal cortical neurons (Hatzipantelis et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, Setoh et al identified another GPR52 agonist, compound 7m, and found that it dose dependently increased [cAMP] i concentrations in CHO cells expressing GPR52 (Setoh et al, 2014). The cAMPincreasing effect of c11 in HEK293 cells expressing GPR52 in our present study was consistent with the result by Setoh et al In addition, recent studies found that 3-BTBZ, another agonist of GPR52, potently increased [cAMP] i in a b-arrestin 2 independent manner in frontal cortical neurons (Hatzipantelis et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Cells were assayed before and after addition of ligands or vehicle. Ligand-induced BRET was calculated by subtracting the ratio of emission through the acceptor wavelength window over emission through the donor wavelength window for a vehicle-treated cell sample from the same ratio for a second aliquot of the same cells treated with ligand(s) where both ratios were corrected by subtracting the baseline value prior to addition of vehicle or ligand . Data are representative of at least three experiments performed in duplicate and are analyzed using GraphPad Prism 9.…”
Section: Methodsmentioning
confidence: 99%
“…Prefrontal cortex Basal ganglia Striatonig 1q25.1 Gαs (Lin et al, 2020) PKA CREB ERK1/2 β-arrestin-2-dependent (Wang et al, 2020a;Hatzipantelis et al, 2020b) Agonists Derivative 17 (Nakahata et al, 2018) Compound 7a: 3-[2-(3-Chloro-5fluorobenzyl)-1-benzothiophen-7yl]-N-(2-ethoxyethyl)benzamide (Setoh et al, 2014) GPR55 central nerve tissues and cells 2q37.1 MAPK/ERK (PI3K)/Akt RhoA-dependent Ca2+ signaling NFAT (Henstridge et al, 2008) Gα12/13-RhoA-ROCK and Gαq-PLC-PKC(88) Gq-G11, mitogenactivated protein kinase 1, and calcium signaling (Henstridge et al, 2008;Andradas et al, 2011) anandamide 2-arachidonoylglycerol 2-arachidonoylglycerolphosphoinositol lysophosphatidylinositol N-palmitoylethanolamine (Ryberg et al, 2007) 2-arachidonoylglycerol N-palmitoylethanolamine JWH015 O-1602 (Ryberg et al, 2007)*…”
Section: Gpr52mentioning
confidence: 99%